Salven mi selva - Zak, Monica, 1939- ([Mexico, D.F.] : SITESA, 1989)
Un nino pide al Presidente de Mexico para proteger la selva Lacandona. [A little boy asks the President of Mexico to save the Lacandona Forest.]
Accelerated Reader AR
Keywords: Conservation of natural resources; Forests and forestry; Spanish language materials; Juvenile literature; Juvenile fiction